Risk-Need-Responsivity applications of the MMPI-2 in sexual offender assessment - Olver, Mark E. (Psychology, crime & law, 2018)
The present investigation examined the risk, need, and responsivity (RNR) correlates of MMPI-2 scores in a Canadian sample of 349 federally incarcerated sex offenders, followed up prospectively 19 years post-release. In terms of responsivity indicators, more serious profile patterns were associated with younger age, single marital status, lower education, and lower cognitive ability; the scales generally had weak associations with sex offender treatment completion or change. With respect to criminogenic risk and need, Scales F, 4, 6, 8, and 9 and combinations therein had significant associations with structured measures of sex offender risk, and in turn, consistently predicted sexual or violent recidivism over 5 and 10-year follow-ups. Several of these predictive associations were maintained even after controlling for static and dynamic risk factors. Finally, model based clustering of the MMPI-2 scales generated three clusters termed disordered, emotionally distressed, and predominantly antisocial (non-disordered) subtypes. Although comparatively higher rates of violent recidivism were found with the disordered subtype, this group did not have higher levels of risk and need, broadly speaking, than the other subtypes. The RNR implications of the results are discussed in terms of forensic applications of MMPI-2 with sex offender populations.